Pobreza multidimensional e participação no programa bolsa família dos domicílios cearenses em 2012 - Andrade, Nathiane Oliveira Celedônio Macedo de (2015)
This research is initially based on a theoretical discussion about poverty in two aspects: monetary and multidimensional. Furthermore it was used Alkire and Foster methodology (2009) to analyze and compare the objectives of “Bolsa Familia” amongst households in Ceara with regards to the PNAD 2012 data. It was also projected two Logit models to identify the socioeconomic characteristics of households that contribute to the classification of poor by income or multidimensional. It was found that , when considering poverty as a multidimensional phenomenon the focus of GMP is worse than under the income aspect . In addition it was estimated that about 40 % of Ceará 's households are poor regardless of the approach used and the higher the population of children and/or elderly at the domicile, the more vulnerable they are to experience a situation of poverty.